(untitled) (Journal of Health Sciences, 2024)
Introduction: As a result of research conducted globally, experts continue to extensively study the long-term consequences that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections can have on patients, as well as the factors contributing to severe outcomes. The aim of this study was to investigate the values of basic biochemical and hematological parameters in patients with fatal outcomes of SARS-CoV-2 infection, as well as to determine the combination of hematological and biochemical parameters that contribute to the progression of SARS-CoV-2 infection. The examined parameters were correlated with the age and gender distribution of patients with fatal outcomes from the SARS-CoV-2 infection. Methods: The study represents a retrospective study of patients hospitalized at the Cantonal Hospital Zenica from February to April 2021, focusing on the biochemical and hematological parameters of subjects with confirmed presence of the SARS-CoV-2 virus using the reverse transcription-polymerase chain reaction methods who were hospitalized at the Cantonal Hospital Zenica. Results: Of the 250 deceased subjects in the sample, females comprised the relative majority at 53.6%. Among the examined parameters, hemoglobin, mean corpuscular hemoglobin (MCH), and MCH were significantly lower in females compared to males, while males had significantly higher values of urea, creatinine, and troponin. The average age of the patients was 74 years, and with aging, the values of erythrocytes, hemoglobin, and troponin increased. Troponin showed a statistically significant positive correlation with age, as well as with urea and creatinine. Conclusion: We can conclude that hemoglobin, urea, creatinine, and troponin are parameters that can be considered to contribute to the progression of SARS-CoV-2 infection. These parameters can be useful for assessing disease severity and prognosis in patients infected with the SARS-CoV-2 virus.